RANCANG BANGUN KINCIR ANGIN SAVONIUS UNTUK MEMBANGKITKAN ENERGI LISTRIK SKALA KECIL - Patabang, Daud (Jurnal MEKANIKAL, 2010)
The aim of this paper is to design and construct a Savonius windmill generating electrical energy in small scale. For generating power 100 watts at wind velocity 4 m/s areÂ find out dimensions of rotor 0.72 m of wideÂ and 0.8 m of height. Rotor is made in two series. The result of experiment at power and wind velocity planning are 51.8% of efficiency and 45.864 watts of power generating